Bureaucratic Residence Regimes and the Integration of Syrian Refugee Women in Spain: A Sociological Analysis with Reference to Germany - Villa, Fernando Gil; Lamsaouri, Salma (International Journal of Criminology and Sociology, 2026)
This article examines how bureaucratic residence regimes shape the integration experiences of Syrian refugee women in Spain, with Germany used as a contextual reference rather than as a fully matched empirical case. Moving beyond dominant integration indicators such as employment, education, and language acquisition, the study argues that legal status and administrative accessibility are constitutive dimensions of integration. The article draws on twenty-six semi-structured interviews with Syrian women residing in Spain and combines these data with an interpretive comparison of the policy and administrative frameworks that structure refugee reception and integration in Spain and Germany. The findings show that residence status is not merely a formal legal category but a lived condition that affects planning, mobility, access to institutions, and emotional security. Interviewees associated bureaucratic complexity with uncertainty, delay, and unequal treatment, and a large majority linked perceived discrimination to bureaucratic settings in Germany. At the same time, interviewees described Spain as relatively more facilitating in terms of residence stability, especially because many had obtained five-year asylum residence permits or had progressed to permanent residence or nationality. The article also highlights the gendered and cultural dimensions of integration, showing how administrative procedures intersect with caregiving responsibilities, language barriers, and differing understandings of family, emotion, and social relations. The study contributes to sociology by conceptualizing bureaucracy as a central mechanism in the production of integration, inequality, and institutional trust. It concludes that integration policy must be understood not only as a matter of social inclusion programming but also as a question of legal architecture and bureaucratic design.